The Talking Toolkit: How smallholding farmers and local governments can together adapt to climate change - Simelton, Elisabeth; Dam, V.B.; Finlayson R; Lasco, Rodel (World Agroforestry Centre, 2013)
The aim of this resource book (or ‘toolkit’) is to help farmers and local governments work together to adapt to climate change. Using the exercises (we call them ‘tools’) described in these pages will help you understand the role of trees and agroforests in reducing the impact of extreme weather events and long-term climate change. The toolkit has been devised by researchers for running focus-group discussions with farmers and other village members by development workers, extension workers or others interested in the climate challenges faced by farmers. These are interdisciplinary and participatory tools that can be used in villages in the early stages of developing adaptation strategies for agriculture, agroforestry and forestry. They include ways of mapping issues in a village, carrying out a household survey, identifying hazards and finding solutions.